Search for heavy Majorana neutrinos in e±e± and e±μ± final states via WW scattering in pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Sanfilippo, Lorenzo; et al. (Physics letters, 2024)
A search for heavy Majorana neutrinos in scattering of same-sign.. boson pairs in proton-proton collisions at root s = 13 TeV at the LHC is reported. The dataset used corresponds to an integrated luminosity of 140 fb(-1), collected with the ATLAS detector during 2015-2018. The search is performed in final states including a same-sign ee or e mu pair and at least two jets with large invariant mass and a large rapidity difference. No significant excess of events with respect to the Standard Model background predictions is observed. The results are interpreted in a benchmark scenario of the Phenomenological Type-I Seesaw model. New constraints are set on the values of the vertical bar V-eN vertical bar(2) and vertical bar VeNV mu N*vertical bar parameters for heavy Majorana neutrino masses between 50 GeV and 20 TeV, where V-eN is the matrix element describing the mixing of the heavy Majorana neutrino mass eigenstate with the Standard Model neutrino of flavour l = e, mu. The sensitivity to the Weinberg operator is investigated and constraints on the effective ee and e mu Majorana neutrino masses are reported. The statistical combination of the ee and e mu channels with the previously published mu mu channel is performed.
Im Titel ist das Sonderzeichen "±" hochgestellt
*the ATLAS Collaboration: G. Aad, A. Ackermann, L.M. Baltes, F. Bartels, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, L. Sanfilippo, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser
Gesehen am 09.09.2025